The Legal System of Public Funds Comparative Study - Ansam Ali Abdullah (الرافدین للحقوق, 2005)
Public utilities were projects created by the state for public benefit, as well as private projects. Public utilities need chattels and real estate so that they can fulfil their tasks and perform their duties in full. Since these funds are of public interest, they require subject to different legal rules The management of private funds, because the public benefit is preferred to the private benefit so that individuals can obtain the services provided by public utilities regularly and continuously